2019
DOI: 10.1038/s41467-019-09687-9
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated nonlinear interactions in graded-index multimode fibers

Abstract: Multimode optical fibers have recently reemerged as a viable platform for addressing a number of long-standing issues associated with information bandwidth requirements and power-handling capabilities. As shown in recent studies, the complex nature of such heavily multimoded systems can be effectively exploited to observe altogether novel physical effects arising from spatiotemporal and intermodal linear and nonlinear processes. Here, we study for the first time, accelerated nonlinear intermodal interactions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 51 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…[ 35 ] The pump relative intensity noise was measured to be 2.1%, and from the 22 mW average output power the peak power coupled to the fiber was estimated to be around 16.5 kW, taking into consideration the Fresnel reflection at the output facet (22.6% for n = 2.67), and 30 dB m −1 propagation loss (6.6 dB for 22 cm fiber length). Given the complex spatio‐temporal nature of SCG in GRIN fibers [ 12,36 ] it is difficult to predict whether coherence is preserved at these conditions, but judging from the output spectrum with increasing pump power there is no indication of modal or geometric instabilities. The fiber's output was imaged to confirm the confinement of light in the fiber's core, as shown in Figure 3e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35 ] The pump relative intensity noise was measured to be 2.1%, and from the 22 mW average output power the peak power coupled to the fiber was estimated to be around 16.5 kW, taking into consideration the Fresnel reflection at the output facet (22.6% for n = 2.67), and 30 dB m −1 propagation loss (6.6 dB for 22 cm fiber length). Given the complex spatio‐temporal nature of SCG in GRIN fibers [ 12,36 ] it is difficult to predict whether coherence is preserved at these conditions, but judging from the output spectrum with increasing pump power there is no indication of modal or geometric instabilities. The fiber's output was imaged to confirm the confinement of light in the fiber's core, as shown in Figure 3e.…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 ] Furthermore, chalcogenides exhibit some of the highest nonlinear refractive indices among known glasses, allowing for the observation of nonlinear optical effects in very short segments of fiber. [ 5–8 ] In the field of nonlinear optics, graded‐index (GRIN) fibers are generating a strong interest for the study of complex multimode beam dynamics, [ 9–12 ] as they enable simultaneous tunability of chromatic and intermodal dispersion. Despite the strong interest, there is no reported example of a GRIN chalcogenide glass fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Lightwave dynamics in multimode waveguides, in particular, have been intensively investigated for their multi-dimensional complexities analogous to other nonlinear systems 2 , 4 6 . So far, various nonlinear dynamics in multimode fibers have been studied, such as accelerated nonlinear interaction 7 , octave supercontinuum generation 8 10 , dispersive wave generation 7 9 , spatial beam self-cleaning 5 , intermodal nonlinear mixing 11 , and self-organized instability 12 , to name a few. More recently, the 3D soliton—a kind of localized wave with particle-like properties—has also been successively discovered in the multimode fiber 13 and the spatiotemporal mode-locking (STML) laser 14 , wherein many transverse and longitudinal modes are simultaneously synchronized to generate 3D femtosecond (fs) solitons.…”
Section: Introductionmentioning
confidence: 99%
“…5 Subsequent experiments have shown that the output transverse spatial distribution at high powers may be controlled, by varying the fiber coupling conditions of the input laser. 8 Nonlinear pulse propagation and beam reshaping in standard or tapered GRIN MMFs [9][10][11] have been investigated in both the normal and in the anomalous dispersion regime, 12,13 using pulses with duration ranging from sub-nanoseconds to femtoseconds. [14][15][16] Active MMFs are key components for a future generation of fiber lasers, which may enable to scale-up by orders of magnitude the peak power of mode-locked laser sources.…”
Section: Introductionmentioning
confidence: 99%